Emergency Control Strategy for High Proportion Renewable Power System Considering the Frequency Aggregation Response of Multi-Type Power Generations - Chang Ye; Kezheng Jiang; Dan Liu; Chunyu Zhang; Di Zhang; Ziwen Liu (IEEE Access)
Large-scale renewable energy grid-connection will lead to a serious weakening of the inertia level of the power grid, which will have a non-negligible impact on the frequency stability of the system. This paper proposes an emergency control strategy for high proportion renewable power system that can make full use of the adjustment ability of multi-type power generations to maximize the frequency recovery effect after disturbances. Firstly, the frequency response characteristics of multi-type power generations in high proportion renewable energy power system are analyzed, and the frequency aggregation response models including thermal power units, wind turbine units and photovoltaic energy storage units are derived. On this basis, a system frequency emergency control model considering the adjustment characteristics of multi-type power generations is established. The objective function of the model is to minimize the frequency modulation cost after disturbance accident, while the constraint conditions include the output power of multi-type power generations and the transient index of frequency stability. The constraint of frequency change rate is transformed into the minimum inertia demand of the system, which can reduce the influence of imprecise measurement of disturbance occurrence time on the accuracy of scheme formulation. Finally, combined with the established example system model, it is verified that the theoretical calculation errors of the maximum frequency deviation and quasi-steady-state deviation against the actual values can be limited within 1% and the effectiveness of proposed emergency frequency control scheme is verified under different disturbances.